CONTRACTUAL SUPPORT FOR INVESTMENT ACTIVITIES - Timush, Iryna; Zhuda, Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to formulate proposals for improving the legal regulation of contractual provision of investment activity and their content. Research methods: general scientific and legal methods of cognition were used, namely: dialectical, comparative analysis, system-functional, formal-legal; logical-legal. Results: it has been proven that a number of business contracts fall under the complex concept of an investment contract; participants in investment activities also conclude other derivative contracts; the main types of contracts used in investment activities are outlined; different types of business contracts in the field of investment are subject to unequal regulatory influence at the level of laws; the risks of investment contracts are partially eliminated by state guarantees; legal regulation of contractual relations in investment activity needs improvement in order to ensure the stability of the investment process and provide additional guarantees and incentives to the investor. It is proposed to legally guarantee the stability of tax and customs payments for subjects of investment contractual relations. At least, it is possible to foresee this at the legislative level for priority areas of investment. Discussion: expediency of distinguishing investment contracts from other investment contracts; legislative consolidation of qualifying features of investment contracts; for the maintenance of investment activities, contracts of various types and, in particular, mixed contracts may be used; legal regulation of contractual investment relations currently mainly concerns investment contracts of a public nature; if the state is a party to such contracts, then its dominant position is clearly observed, which indicates a deviation from the principle of equality of the parties.